The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/23279095.2017.1298600
|View full text |Cite
|
Sign up to set email alerts
|

Utility of critical items within the Recognition Memory Test and Word Choice Test

Abstract: This study was designed to examine the clinical utility of critical items within the Recognition Memory Test (RMT) and the Word Choice Test (WCT). Archival data were collected from a mixed clinical sample of 202 patients clinically referred for neuropsychological testing (54.5% male; mean age = 45.3 years; mean level of education = 13.9 years). The credibility of a given response set was psychometrically defined using three separate composite measures, each of which was based on multiple independent performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 65 publications
7
22
0
Order By: Relevance
“…This finding is consistent with suggestions that embedded PVTs may be less robust to cognitive impairment compared to stand-alone PVTs (Zenisek et al, 2016). For instance, findings regarding the utility of LM-II-R appear mixed, and recent studies have shown that it has inadequate classification accuracy compared to other commonly used PVTs (e.g., WC) and mixed specificity and sensitivity in clinical samples, including those with cognitive impairment (Bain et al, 2019;Erdodi, Tyson, et al, 2018;Greve et al, 2008;Miller et al, 2011;Soble et al, 2018;Webber & Soble, 2018). Thus, the current findings highlight the need for further research examining performance patterns using embedded PVTs in populations with severe cognitive impairment, given their inextricable relation to cognitive ability.…”
Section: Discussionsupporting
confidence: 85%
“…This finding is consistent with suggestions that embedded PVTs may be less robust to cognitive impairment compared to stand-alone PVTs (Zenisek et al, 2016). For instance, findings regarding the utility of LM-II-R appear mixed, and recent studies have shown that it has inadequate classification accuracy compared to other commonly used PVTs (e.g., WC) and mixed specificity and sensitivity in clinical samples, including those with cognitive impairment (Bain et al, 2019;Erdodi, Tyson, et al, 2018;Greve et al, 2008;Miller et al, 2011;Soble et al, 2018;Webber & Soble, 2018). Thus, the current findings highlight the need for further research examining performance patterns using embedded PVTs in populations with severe cognitive impairment, given their inextricable relation to cognitive ability.…”
Section: Discussionsupporting
confidence: 85%
“…PVTs are usually forced-choice recognition tests, in which a patient, in the presence of a foil, must identify the stimuli which have previously been presented (Blaskewitz, Merten, & Kathmann, 2008;Gervais, Rohling, Green, & Ford, 2004). Although PVTs have been widely studied (Armistead-Jehle, Lange, & Green, 2017;Bianchini, Mathias, & Greve, 2001;Erdodi et al, 2017;Gast & Hart, 2010;Reslan, & Axelrod, 2017;Simões, 2006), a few research issues have emerged over the years.…”
mentioning
confidence: 99%
“…Diagnoses were determined by the assessing clinicians based on Diagnostic and Statistical Manual of Mental Disorders , Fifth Edition ( DSM-5 ; APA, 2013) criteria using available medical records, clinical interviews, and psychometric data. A portion of the sample was used in previous publications focused on different topics (Erdodi, 2019; Erdodi et al, 2017; Erdodi, Dunn, et al, 2018; Erdodi, Hurtubise, et al, 2018; Erdodi & Lichtenstein, 2017; Erdodi, Pelletier, & Roth, 2018; Erdodi & Roth, 2017; Erdodi, Sagar, et al, 2018; Erdodi, Seke, et al, 2017; Erdodi, Tyson, et al, 2017, 2018; Rai & Erdodi, 2019; Zuccato et al, 2018). The only inclusion criterion was having data available on the Five-Variable Psychiatric Screener (V-5).…”
Section: Methodsmentioning
confidence: 99%